2014
DOI: 10.5858/arpa.2013-0309-oa
|View full text |Cite
|
Sign up to set email alerts
|

Folate Receptor α Associated With Triple-Negative Breast Cancer and Poor Prognosis

Abstract: Our data demonstrate that a significant subgroup of ER/PR-negative and triple-negative breast cancers express FRA, and its expression is associated with worse clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
84
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(90 citation statements)
references
References 21 publications
5
84
1
Order By: Relevance
“…The overexpression of FR protein has been confirmed in all clinical breast cancer subtypes, comprised of estrogen receptor-positive (ER+), progesterone receptor-positive (PR+), human epidermal growth factor receptor-positive (HER2+), and triple negative (ER−, HER2−, and PR−) tumors [16][17][18]. Recent polymerase chain reaction studies confirmed that FR is highly expressed in T47D cells [19].…”
Section: Introductionmentioning
confidence: 99%
“…The overexpression of FR protein has been confirmed in all clinical breast cancer subtypes, comprised of estrogen receptor-positive (ER+), progesterone receptor-positive (PR+), human epidermal growth factor receptor-positive (HER2+), and triple negative (ER−, HER2−, and PR−) tumors [16][17][18]. Recent polymerase chain reaction studies confirmed that FR is highly expressed in T47D cells [19].…”
Section: Introductionmentioning
confidence: 99%
“…A study of breast carcinomas showed FRA protein expression was associated with triplenegative status and high histologic grade. 2 Conversely, a study of endometrial carcinomas showed FRA protein expression was associated with low histologic grade. 4 No relationship between FRA protein expression and histologic grade was observed for ovarian and colorectal carcinomas.…”
mentioning
confidence: 99%
“…This glycosyl-phosphatidylinositol-anchored protein not only serves to bind and transport folate intracellularly, but has also been shown to promote proliferation in cells expressing the receptor, especially in low-folate environments [30]. It has been observed that FRA expression is negatively regulated by ER, and that downregulating ER with antiestrogen agents, such as tamoxifen, increases further FRA expression [22,31], which has also been observed with a poor prognosis [23]. The limited normal tissue distribution of FRA and its overexpression in certain malignancies makes FRA a promising target for directed therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, investigators have examined the prognostic significance of FRA expression in breast carcinoma and found a potential clinical usefulness of FRA overexpression as a prognostic biomarker [21,22,23]. Nonetheless, the utility of FRA as a diagnostic marker of metastatic breast carcinoma in cytology specimens has not been fully established.…”
Section: Introductionmentioning
confidence: 99%